Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2007
DOI: 10.1007/s10592-007-9321-3
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of microsatellite loci in the black rhinoceros (Diceros bicornis) and white rhinoceros (Ceratotherium simum): their use for cross-species amplification and differentiation between the two species

Abstract: As the population sizes of the black and white rhinoceroses continues to decline, more efforts are needed in multiple areas to help with the conservation efforts. One area being explored is the use of genetic diversity information to aid conservation decisions. In this study, we designed 21 microsatellite primers for white and black rhinoceroses, 16 and 17 of which amplified bands in the white and black rhinoceros, respectively. Out of these primers all 16 were polymorphic in the white rhinoceros and 12 of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 8 publications
2
8
0
Order By: Relevance
“…It is apparent that low levels of genetic diversity characterize southern white rhinoceros populations, and the results from our study are consistent with other microsatellite studies in this species (Seror et al 2002;Florescu et al 2003;Nielsen et al 2008 To date, our study population has produced just one inbred F 2 individual from seven offspring in the F 2 cohort. While many species demonstrate deleterious effects from inbreeding depression (Frankham et al 2002), in both managed and natural populations of free-ranging, long-lived species these effects are very difficult to measure.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…It is apparent that low levels of genetic diversity characterize southern white rhinoceros populations, and the results from our study are consistent with other microsatellite studies in this species (Seror et al 2002;Florescu et al 2003;Nielsen et al 2008 To date, our study population has produced just one inbred F 2 individual from seven offspring in the F 2 cohort. While many species demonstrate deleterious effects from inbreeding depression (Frankham et al 2002), in both managed and natural populations of free-ranging, long-lived species these effects are very difficult to measure.…”
Section: Discussionsupporting
confidence: 91%
“…Loci were selected based on data from Coutts (2009) and included 7B and 7C (Florescu et al 2003), WR1 and WR2 (reported in Nielsen et al 2008, redesigned from loci reported in Florescu et al 2003), BR6 (Cunningham et al 1999), DB1, DB44 and DB49 (Brown and Houlden 1999) and Rh7, Rh8 and Rh9 (Zschokke et al 2003). PCR conditions followed Coutts (2009) and Menotti-Raymond et al (2005) and cycle conditions were 5 adapted where needed (see Online Resource S2 for details).…”
Section: Dna Extraction and Microsatellite Genotypingmentioning
confidence: 99%
“…Within our study, the average H E for D. b. minor was estimated at 0.44 compared with 0.51 reported for D. b. bicornis (Harley et al, 2005) and 0.68 for D. b. michaeli (see also Brown & Houlden, 1999) (in our study, H E was estimated at 0.43 for D. b. bicornis and 0.54 for D. b. michaeli based on a sample size of four individuals per subspecies). Although the lower heterozygosity for D. b. minor may reflect a sampling bias in our study, we do not believe this to be the case as our finding are in line with previous studies which similarly documented lower diversity within D. b. minor (H E = 0.46, Harley et al, 2005; H E = 0.37, Nielsen et al, 2008). Rather, these lower diversity values may reflect past demography and a small founding population (both in terms of number of individuals as well as the geographic area from which samples were taken) where all extant South African D. b. minor individuals are descendants from populations on only two reserves namely Hluhluwe-iMfolozi Park and Mkhuze Game Reserve.…”
Section: Discussionsupporting
confidence: 81%
“…Earlier genetic studies of black rhinoceros have examined various aspects of ex-situ conservation using mitochondrial (mt; Ashley et al 1990;Jama et al 1993; Morales and Melnick 1994;O'Ryan et al 1994) and nuclear DNA (Brown and Houlden 1999;Garnier et al 2001;Zschokke et al 2003;Nielsen et al 2008;Scott 2008). For example, Swart et al (1994), using mtDNA, demonstrated the persistence of genetic diversity in small populations of black rhinoceros that had undergone demographic contraction; highlighting the need to conserve even small populations.…”
Section: Introductionmentioning
confidence: 99%